WORKSHOP KARYA TULIS ILMIAH BERBASIS PELATIHAN SPSS DAN SEM-PLS UNTUK MENINGKATKAN KUALITAS TUGAS AKHIR MAHASISWA - Eko Giyartiningrum; Retno Kurnianingsih; Heri Prasetyo; Ika Destina Puspita (JURNAL PENGABDIAN MANDIRI, 2026)
Final-year students frequently encounter significant obstacles in completing their undergraduate theses, particularly regarding statistical anxiety and limited technical skills in quantitative data analysis. This community service activity aims to enhance students' methodological capacity and practical skills through a Scientific Writing Workshop based on SPSS and SEM-PLS Training. The workshop was conducted on May 23, 2026, at Universitas Cokroaminoto Yogyakarta, involving final-year students from Management and Accounting study programs. The implementation method employed an experiential learning approach, combining theoretical lectures and hands-on practice across two main sessions: Session 1 focused on multiple linear regression analysis and classical assumption tests using SPSS 25, while Session 2 focused on complex model analysis (mediation and moderation) using SEM-PLS 4. The program's effectiveness was evaluated using pre-test, post-test, and participant satisfaction questionnaires. The evaluation results demonstrated a significant increase in participants' technical understanding and statistical interpretation, rising from an average pre-test score of 26.7% (fair/low category) to 88.6% in the post-test (high category). Furthermore, 93.3% of participants expressed high satisfaction and found the material directly relevant to their thesis completion needs. This workshop proved effective in reducing statistical anxiety and improving the academic quality of students' results and discussion chapters.